Muscle clamp as the form of primitive psychological defense - Vaskivska, Svetlana; Szulik, Maria (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
This article describes the results of the research, which empirically confirms the existence of connection between psychologica l defenses, early parental drivers/restrictions and muscle spasmes in the hum an body. According to our findings of muscle spasmes are archaic unconscious foundation for the further formation of the variety of psychological defence of the person. They co me at a time when the psychicsphere performance is not desomatized. Analysis of architectonic muscle spasmes allows to speak about a single ontigenetic primary psychological defensemechanism – protossome. This mechanism manifestation is specific for each concrete person and imprinted in the "Self-image". Bodily experience, because of early formation, is not able to be acting out, it accumulated and manifested in new, even more complex symptoms. Representation discovered specific psychological defense mechanisms connections with features of muscle spasmes facilitate our work in therapy, allowing to work with formations of preverbal period.